Sertifikasi Halal dan Kesadaran Halal Pada Minat Beli Produk Makanan - Adinda Choirul Ummah; Moh. Bahrudin; Syamsul Hilal (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Food products are products of primary human needs, so they are needed. In Muslim societies, food products have provisions related to halal food so that they comply with the Shari'a. However, many products, especially in Indonesia, are still unclear about their halal status, which can influence buying interest. In addition, public awareness of halal is also important because it is considered to influence buying interest. The purpose of this study is to determine the effect of halal certification and halal awareness on consumer buying interest. This research method is a quantitative method with primary data in the form of interviews using a Likert scale. The results showed that halal certification had a significant positive effect on consumer buying interest as indicated by the tcount (5.946) > ttable (1.971). The more products that have halal certificates, the more consumers' buying interest will increase. Then the results of the study also show that halal awareness has a positive effect on consumer buying interest as indicated by the tcount (8.640) > ttable (1.971). That is, the higher the awareness of halal, the higher the consumer's buying interest.